(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Great Depression had affected all aspects of life in America. Poverty, unemployment, housing-problems, strained family relations, strikes, agitations and protest-movements had become the order of the day. But the most important and positive result of the depression, however, was that it gave ample scope to the writers to write on a variety of topics-social, economic, political and psychological. The change in the social climate of the thirties from prosperity to adversity marked the rapid development of the literature of protest and the so-called left-wing literature and made the writers of the period more explicit and realistic in their approach. As a matter of fact, the tradition of protest and revolt had been dominant in American literature since Emerson and Thoreau, but then, as Henry Steel Commager points out in The American Mind, protest had been, for the most part, political or social rather than economic (1950). In contrast, the literature of the thirties was essentially a literature of socio-economic protest. The bitterest protesters of the ailing economy were revolutionary writers-Marxists, Communists and fellow travellers-whoused literature as propaganda to present their political perspectives. They highlighted the blemishes of capitalism, glorified the little people and made their art virtually a weapon to attack the social and political evils. In his essay entitled Theatre and Living, Tynan asserts... the artist and particularly the dramatist, is forced to involve himself with political issues, to immerse himself in the world of which he is a part. Art which ignores social questions is a shrinking flower that conspires at its own death by ignoring the soil in which it grows(94-95).